Oxygen treatment reduces neurological deficits and demyelination in two animal models of multiple sclerosis. Issue 1 (10th January 2023) - Amatruda, Mario; Harris, Kate; Matis, Alina; Davies, Andrew L.; McElroy, Daniel; Clark, Michael; Linington, Christopher; Desai, Roshni; Smith, Kenneth J.
Abstract: Aims: The objective of the study is to explore the importance of tissue hypoxia in causing neurological deficits and demyelination in the inflamed CNS, and the value of inspiratory oxygen treatment, using both active and passive experimental autoimmune encephalomyelitis (EAE). Methods: Normobaric oxygen treatment was administered to Dark Agouti rats with either active or passive EAE, compared with room air‐treated, and naïve, controls. Results: Severe neurological deficits in active EAE were significantly improved after just 1 h of breathing approximately 95% oxygen. The improvement was greater and more persistent when oxygen was applied either prophylactically (from immunisation for 23 days), or therapeutically from the onset of neurological deficits for 24, 48, or 72 h. Therapeutic oxygen for 72 h significantly reduced demyelination and the integrated stress response in oligodendrocytes at the peak of disease, and protected from oligodendrocyte loss, without evidence of increased oxidative damage. T‐cell infiltration and cytokine expression in the spinal cord remained similar to that in untreated animals. The severe neurological deficit of animals with passive EAE occurred in conjunction with spinal hypoxia and was significantly reduced by oxygen treatment initiated before their onset. Conclusions: Severe neurological deficits in both active and passive EAE can be caused by hypoxia and reduced by oxygen treatment. Oxygen treatment also reduces demyelination in active EAE, despite the autoimmune origin of the disease. Abstract : Neuroinflammation can cause CNS hypoxia. The inflamed CNS of rats with experimental autoimmune encephalomyelitis (EAE, a model of multiple sclerosis) is hypoxic. Normobaric oxygen treatment of rats with EAE restores a normal CNS oxygenation and decreases the magnitude of both neurological deficit and histological signs of CNS damage. This finding demonstrates the role of tissue hypoxia to the pathobiology of neuroinflammatory diseases, and the potential value of oxygen as a therapy.